Bank capital, government bond holdings, and sovereign debt capacity - Crosignani, Matteo (Journal of Financial Economics, 2021)
I develop a model where the sovereign debt capacity depends on the capitalization of domestic banks. Low-capital banks optimally tilt their government bond portfolio toward domestic securities, linking their destiny to that of the sovereign. If the sovereign risk is sufficiently high, low-capital banks lend less to the productive sector to further increase their holdings of domestic government bonds, lowering sovereign yields. In this case, a government that regulates bank capital faces a trade-off. On the one hand, high-capital banks lend more to the productive sector. On the other hand, low-capital banks support the home sovereign debt capacity.